2020
DOI: 10.18502/jbe.v6i1.4754
|View full text |Cite
|
Sign up to set email alerts
|

Moral Sensitivity among Nursing and Midwifery Students and Practitioners: a Comparative Report from Iran

Abstract: Background: Ethical sensitivity refers to knowledge and practice of ethical issues in a contradictory situation highlighted with self-awareness of one’s role and duty in those particular situations. According to ethics of care, the caregiver is committed to continuous learning and practicing the right options. The present study aimed to compare the moral sensitivity of midwifery and nursing students with that of nurses and midwives in Sabzevar University of Medical Sciences, Iran. Materials and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the present study, the ethical sensitivity of the participants during the pandemic was also examined, and no significant change was found. Before the pandemic, studies examining the ethical sensitivity of nursing students in the literature revealed that the ethical sensitivity of the students is at a medium‐high level (Bayrak Aykan et al., 2019 ; Hançerlioğlu et al., 2020 ; Hoseini et al., 2020 ; Kilic Akca et al., 2017 ) supporting this study. Nurses often have ethical problems in practice.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study, the ethical sensitivity of the participants during the pandemic was also examined, and no significant change was found. Before the pandemic, studies examining the ethical sensitivity of nursing students in the literature revealed that the ethical sensitivity of the students is at a medium‐high level (Bayrak Aykan et al., 2019 ; Hançerlioğlu et al., 2020 ; Hoseini et al., 2020 ; Kilic Akca et al., 2017 ) supporting this study. Nurses often have ethical problems in practice.…”
Section: Discussionsupporting
confidence: 70%
“…Overall, ethical sensitivity is extremely important for health care and treatment as it shapes nurses ability of ethical decision‐making. Therefore, student nurses should develop ethical sensitivity during their academic education (Hançerlioğlu et al., 2020 ; Hoseini et al., 2020 ). For nursing students to become nurses with a developed sense of ethics after graduation, they must first be aware of their own emotions, thoughts and values, and also undergo an education programme that provides the capacity to deal with the ethical dilemmas brought by the patient care (Hançerlioğlu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scale, extrinsic religious orientation is rated on a 4-point Likert scale as follows: Completely disagree (5), somehow disagree (4), agree (2), and completely agree (1). For the intrinsic religious orientation scale, the rating is as follows: Completely agree (1), somehow agree (2), agree rather than not (4), and completely disagree (5). The lowest score is given to people expressing intrinsic religious orientation (i.e., scores between 9 and 45), and the highest score is given to those with extrinsic religious orientation (i.e., scores between 11 and 55).…”
Section: Religious Orientation Scalementioning
confidence: 99%
“…This is because the future decisions made by nurses in their work environments are closely tied to moral considerations. These decisions not only have an impact on the lives of patients but also influence the quality of the care provided (5). Research has shown that nursing students with higher levels of moral courage demonstrate greater professional commitment, enabling them to advocate for the rights and needs of their patients.…”
Section: Introductionmentioning
confidence: 99%